Natural Ventilation and Energy Consumption Research for Dry Sports Halls Within National Fitness Centers in Cold Regions—Case Study of Qingdao - Wen Zhang; Lingling Li; Yu Li (Buildings)
The lack of energy-saving design in national fitness centers has affected low-cost operation and indoor comfort. Existing studies mainly focus on the impact of lighting and heat on energy consumption in sports stadiums, highlighting the need for the comprehensive planning of natural ventilation design to improve energy efficiency. This study uses the national fitness center in Qingdao as a case study, collecting building environmental information through field measurements and questionnaire surveys. Four design elements were selected: the window-to-wall ratio (WWR), proportion of operable window area (OWAR), skylight area ratio (SAR), and floor plan layout. Through the utilization of Ladybug Tools in combination with Radiance and EnergyPlus, an annual energy consumption simulation under natural ventilation conditions was conducted using an airflow network model. This study found that the WWR has a significant impact on lighting, ventilation, and energy consumption. The optimal WWR configuration for the venue was determined to be 0.37 for the north facade, 0.26 for the east, 0.53 for the south, and 0.41 for the west. Compared to no natural ventilation, cooling energy consumption was reduced by 18.02%, and fan energy consumption decreased by 11.03%. The energy-saving effect was optimal when the OWAR was approximately 30%. When the SAR reached 5%, cooling and lighting energy consumption were significantly reduced, resulting in the lowest total energy consumption. The study also compared the energy consumption differences in various floor plan layouts under the influence of natural ventilation. This research evaluates the natural ventilation efficiency of community fitness centers, avoiding the hidden energy consumption transfer typical of traditional single-objective optimization methods, and improves the energy-efficient design approach for national fitness centers.